Identifikasi Potensi Swasembada Beras di Sumatera Utara - Ridwan Fadly; Yusniar Lubis; Faoeza Hafiz Saragih (Jurnal Ilmiah Pertanian ( JIPERTA), 2020)
This study aims to determine the potential of districts in North Sumatra Province in an effort to increase rice production in North Sumatra Province. The type of data used in this study is secondary data. The basic method used is descriptive analysis research method. The analytical tool used is Shift Share Analysis (SSA). The results of this study indicate; 1) districts that have potential harvested area in North Sumatra Province are Nias Barat district, Mandailing Natal District, South Tapanuli District, North Padang Lawas Regency, Central Tapanuli Regency, South Nias Regency, Padang Sidempuan Regency, Gunung Sitoli Regency, Tapanuli Regency North, Simalungun Regency, Binjai Regency, Labuhan Batu Regency, Langkat Regency; 2) Districts that have rice production potential in North Sumatra Province are Nias Regency, West Nias Regency, Mandailing Natal Regency, Padang Lawas Utara Regency, South Nias Regency, Padang Sidempuan District Gunung Sitoli, Tapanuli Utara Regency, Toba Samosir Regency, Regency Simalungun, Karo Regency, Batu Bara Regency, Asahan Regency, Binjai Regency; 3) Districts in North Sumatra Province which are the most potential areas, in the harvest area is North Padang Lawas Regency and the most potential area in rice production is Simalungun Regency